Peran Moderasi Komitmen Organisasi dalam Hubungan Faktor Personal Auditor dan Deteksi Kecurangan di Sektor Publik - Mahardhika Hadi Kusuma; Amrie Firmansyah (Politeknik Ganesha Medan, 2025)
This research aims to examine the effect of auditor personal factors on the ability of auditors to detect fraud with organizational commitment as a moderator. The research was conducted with the auditors of the Supreme Audit Agency. The resource persons were selected from the population based on purposive sampling and the final sample used in this research was 64. Data analysis was carried out using a structural equation model. The results show that the auditor's personal factors positively affect the auditor's ability to detect fraud. However, organizational commitment failed to moderate the relationship between these two variables. This condition is thought to be because most respondents are employees with long service periods, so organizational commitment is not an important factor in detecting fraud. This research contributes to fraud literature and contributes to stakeholders in formulating human resource policies. Furthermore, testing auditors' ability to detect fraud in the public sector is still rare in previous literature, especially with goal orientation and self-efficacy. In addition, the use of organizational commitment as a moderating variable in this relationship can complement the public sector audit literature in Indonesia.